A Cross-sectional Survey of HIV Transmission and Behavior among Men Who Have Sex with Men in Different Areas of Inner Mongolia Autonomous Region, China. (December 2016) - Qu, Lin; Wang, Wenrui; Gao, Yongming; Yang, Jingyuan; Dai, Jijiang; Wang, Dawei; Tao, Bo
Abstract Background Little research has been conducted on the human immunodeficiency virus (HIV) epidemic and the sexual intercourse habits of men who have sex with men (MSM) in crowded places, both locally and abroad. This study conducted a survey of MSM in different locales of Inner Mongolia to provide a reference for developing strategies or measures to prevent and control HIV among this understudied population. Methods We conducted a cross-sectional survey of men aged 18 years and older at different venues popular among MSM in Inner Mongolia. Between April and July 2012, MSM volunteered to participate in this study, receive HIV/syphilis testing, and complete a questionnaire about their behavior. A total of 1611 MSM participated. Participants signed a voluntary informed consent form, completed an anonymous questionnaire and were tested for HIV and syphilis antibodies. Results Of the 1611 MSM surveyed, 6.83 and 23.65 % had HIV and syphilis, respectively, and the co-infection rate was 3.17 %. Sociodemographic factors such as age, culture, marital status, knowledge of acquired immune deficiency syndrome (AIDS) transmission, and peer education significantly differed between venues (P < 0.01). MSM who were under 22 years, 23–35 years, and over 36 years primarily contacted their potential partners online, at bars/other (streetwalkers), and at public baths/parks, respectively. MSM partners found in bars, in public baths, in parks and online were primarily high school students and technical secondary school students. MSM who were streetwalkers or cross-dressing male sex workers primarily had junior middle school education levels or below. Married MSM primarily had intercourse in public baths and parks, and MSM who had intercourse in public baths and parks also reported the greatest proportions of intercourse with women (39.1 and 35.0 %, respectively). Furthermore, MSM who had intercourse in parks reported having the most anal sex with same-sex partners and unprotected intercourse in the past 6 months. Unprotected intercourse with women in the past 6 months was also common among MSM who met partners in bathhouses or online. MSM were most likely to have anal sex with other men in public baths. MSM who had intercourse in bars were the least likely to have used a condom with female partners in the past 6 months. The culture of the MSM who had frequent intercourse with streetwalkers and cross-dressing male sex workers did not predict behavior. Conclusion This study indicated that AIDS-related risky behaviors as well as HIV and syphilis infection were associated with the different locations frequented by MSM. When developing intervention strategies for AIDS, it is better to conduct targeted health education and behavioral interventions at bars/online for MSM aged 23–35 years and at public baths/parks for MSM over 36 years. Additionally, the current survey showed that information on AIDS/sexually transmitted diseases (STDs) must be popularized to reach streetwalkers and cross-dressing male sex workers, whose mobility limits their attainment of higher levels of health education.